Short‐term histological evaluations after achieving a sustained virologic response to direct‐acting antiviral treatment for chronic hepatitis C. Issue 9 (1st November 2018) - Enomoto, Masaru; Ikura, Yoshihiro; Tamori, Akihiro; Kozuka, Ritsuzo; Motoyama, Hiroyuki; Kawamura, Etsushi; Hagihara, Atsushi; Fujii, Hideki; Uchida-Kobayashi, Sawako; Morikawa, Hiroyasu; Murakami, Yoshiki; Kawada, Norifumi
Abstract : Background: Interferon‐free, direct‐acting antiviral treatments can result in a sustained virologic response in nearly 100% of patients with chronic hepatitis C virus infection. Aims: The purpose of this study was to evaluate histological improvement after achieving a sustained virologic response to direct‐acting antiviral treatments in patients with chronic hepatitis C. Methods: Among 691 patients with chronic hepatitis C who achieved a sustained virologic response to direct‐acting antivirals, 51 underwent liver biopsy 41 ± 20 weeks after the end of treatment despite normal transaminase levels. In 20 patients, liver biopsy specimens obtained a median of 1.2 years before the start of treatment were available. Results: Among the 51 patients who underwent post‐sustained virologic response biopsies, the grade of inflammation was A0 in 18 patients, A1 in 24, A2 in eight, and A3 in one; the stage of fibrosis was F0 in three patients, F1 in 20, F2 in 15, F3 in nine, and F4 in four. Among the nine post‐sustained virologic response biopsy specimens with moderate‐to‐severe inflammation (≥A2), four showed S1‐to‐S3 steatosis (>5% of hepatocytes affected). In the 20 paired biopsy specimens, the inflammation grade significantly regressed ( p  = 0.0043), but the fibrosis stage did not ( p  = 0.45). Histological improvement, defined as a ≥ 2‐point decrease in the Knodell inflammatory score and no worsening of the fibrosis, was found in 11 (55%) patients. The iron accumulation had significantly regressed ( p  = 0.0093), but the steatosis had not ( p  = 0.10). Conclusions: Even if transaminases become normal after obtaining a sustained virologic response, significant histological inflammation of unknown cause was found in some patients. Additionally, improvement in liver fibrosis was not evident in the short term.